2020
DOI: 10.1186/s40942-020-00223-2
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal nevus and polypoidal vasculopathy: case series

Abstract: Background To report an association between choroidal nevus and polypoidal choroidal vasculopathy (PCV) in three patients. Case presentation We have encountered 3 isolated patients in our center presenting with subretinal exudation and a choroidal nevus that were thoroughly evaluated by slit lamp biomicroscopy, fundus photos, Fluorescein angiography (FA), indocyanine green angiography (ICG), B-scan ultrasound, and optical coherence tomography (SD-OCT—Heidelberg). The classic features of choroidal neovasculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“… 4 Moreover, almost a dozen cases of association between polypoidal lesions and choroidal nevi have been described. 5 12 This association may indicate a link between choroidal nevi and the pachychoroidal spectrum proposed by some authors. So far until now, the relationship between choroidal nevi and pachychoroidal disorders has not been studied.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“… 4 Moreover, almost a dozen cases of association between polypoidal lesions and choroidal nevi have been described. 5 12 This association may indicate a link between choroidal nevi and the pachychoroidal spectrum proposed by some authors. So far until now, the relationship between choroidal nevi and pachychoroidal disorders has not been studied.…”
Section: Introductionsupporting
confidence: 54%
“…These findings also correlate with a growing number of reports on coincidence of choroidal nevi and polypoidal lesions since both CSCR and polypoidal vasculopathy belong to the pachychoroidal spectrum. [5][6][7][8][9][10][11][12] Dark-field SLO, a modification of confocal infrared SLO, used in this study previously demonstrated a high sensitivity and specificity in the detection of the choroidal nevi with an area under the ROC curve of 1.0. 13 This fact as well as routine documentation of the CSCR cases using this option in our center allowed us to conduct this study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The first report about polypoidal lesions in association with choroidal nevi was published in 2009 by Peiretti et al 8 Since then, single cases have been reported. 9–15 Although many cases can be safely observed, some require treatment with intravitreal antivascular endothelial growth factor (VEGF) injections, 12,16 photodynamic therapy, 9,13 or focal argon laser. 14…”
mentioning
confidence: 99%
“…7 The first report about polypoidal lesions in association with choroidal nevi was published in 2009 by Peiretti et al 8 Since then, single cases have been reported. [9][10][11][12][13][14][15] Although many cases can be safely observed, some require treatment with intravitreal antivascular endothelial growth factor (VEGF) injections, 12,16 photodynamic therapy, 9,13 or focal argon laser. 14 The aim of this multicenter study was to investigate multimodal imaging characteristics of polypoidal lesions associated with choroidal nevi, and their clinical course over a long follow-up period.…”
mentioning
confidence: 99%